This land is my land. You wish! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Gender perspectives on property and inheritance. A Global Source Book Vol. 5, the Gender, Society & Development series By S Cummings, H van Dam, A Khadar & M Valk, KIT Publishers, 2001. 180 pp. ISBN 90 6832 714 3 Euro 22